2008
DOI: 10.1109/tvcg.2008.125
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Animation in Trend Visualization

Abstract: Abstract-Animation has been used to show trends in multi-dimensional data. This technique has recently gained new prominence for presentations, most notably with Gapminder Trendalyzer. In Trendalyzer, animation together with interesting data and an engaging presenter helps the audience understand the results of an analysis of the data. It is less clear whether trend animation is effective for analysis. This paper proposes two alternative trend visualizations that use static depictions of trends: one which show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
245
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(259 citation statements)
references
References 11 publications
(9 reference statements)
12
245
1
1
Order By: Relevance
“…Applications of this framework include visualizing software evolution [24], social networks analysis [9], and the behavior of dynamically modifiable code [30]. Robertson et al [89] evaluate the effectiveness of three trend visualization techniques. The results indicate that animation, often enjoyable and exciting, is not always well suited to data analysis.…”
Section: Animation Versus Small Multiplesmentioning
confidence: 99%
“…Applications of this framework include visualizing software evolution [24], social networks analysis [9], and the behavior of dynamically modifiable code [30]. Robertson et al [89] evaluate the effectiveness of three trend visualization techniques. The results indicate that animation, often enjoyable and exciting, is not always well suited to data analysis.…”
Section: Animation Versus Small Multiplesmentioning
confidence: 99%
“…However, as emphasized in the introduction, only a few different colours and bubble sizes can be readily distinguished by visual inspection, and there may be perceptual interference between colour and size coding (Healey, 2000;Bartram, 2001). In addition, it should be mentioned that static visualizations, such as a small multiples display, are still viable alternatives to animated graphs (Robertson et al, 2008). Much of the work presented here was inspired by Rosling and co-workers (Gapminder, 2011), who demonstrated that the animated bubble chart is a powerful tool for visualizing temporal trends in official statistics and other data collected annually for a set of objects.…”
Section: Discussionmentioning
confidence: 99%
“…The use of animated population pyramids in official statistics (the Australian Bureau of Statistics, 2011) illustrates that almost any static graph in statistics can be animated to visualize changes over time. However, some authors have emphasized that animations are not always superior to static presentations such as a small multiples display (Robertson et al, 2008). Visualization of temporal changes in the size and shape of 2D point clouds represents yet another approach that is particularly suitable for exploring large datasets (Landesberger et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Visualizing trends in time-varying and multi-variate data has been considered in depth within the information visualization community [6]. However, for visualization of biomechanical motion over time, 3D views of the model are often animated, and additional data attributes are often visualized using color, texture, streamlines, and 3D data glyphs [2,7,8].…”
Section: Related Workmentioning
confidence: 99%
“…However, for visualization of biomechanical motion over time, 3D views of the model are often animated, and additional data attributes are often visualized using color, texture, streamlines, and 3D data glyphs [2,7,8]. While these annotated 3D views can be quite powerful, it has been suggested that understanding trends over time through animation may not be the most effective strategy [6]. Our system follows the framework developed by Keefe et al [3] in that we also utilize a multiple coordinated visualization approach and support analysis using both the 3D model view and 2D information visualizations.…”
Section: Related Workmentioning
confidence: 99%